A Concept of counter vailing power in maritime affairs-central freight bureau of Sri Lanka - Gunaratne, M.H. (My University, 2012)
The practices of liner Conferences had evoked concern of governments a quarter of a century after the formation of the first liner Conference in 1875. The Royal Commission on Shipping Ring (1909) pioneered the cause of a dialogue between shippers and ship-owners in Shippers' Councils as against public regulation recognised in the U.S.A. by the Merchant Marine Act of 1916. In other countries regulation has been restricted to specific aspects of Conference practices and such control as exists is comparatively recent in origin. The vision of the Royal Commission took nearly a half a century to materialise in the first British Shippers' Council. Following its establishment in 1955 Western European Countries established their own councils and in developing countries they were established following the initiative of UNCTAD after 1964. The subsequent developments in this context witnessed the birth of the CENSA Code of Practice and the Code of Conduct for Liner Conferences. The institution of the Central Freight Bureau of Sri Lanka has been evaluated as a link in the chain of events leading to regulation of Conferences. The objectives of the Bureau are analysed to arrive at a hypothesis that Conferences could be regulated by strengthening shippers bargaining position by performing well integrated functions in the provision of economic loads for calling liners maintaining efficient port services, developing a competent service in national lines, and widening shippers' knowledge on comparative shipping problems forming the nucleus in the development of effective consultation machinery. Satisfactory results have been brought out in analyzing the Bureau's achievements during its short period of existence.